Structural design of tetravalent T-cell engaging bispecific antibodies: improve developability by engineering disulfide bonds - Yu, Lin; Huang, Nan; Ge, Liangpeng; Sun, Heng; Fu, Yuna; Liu, Chundong; Wang, Jianhua (Journal of biological engineering, 2021)
Since the advances in protein engineering and manufacture, over the last 30 years, antibody-based immunotherapeutic has become a powerful strategy to treat diseases. The T-cell engaging bispecific antibody (BsAb) by combining the Fab binding domain of tumor antigens and Fab or single-chain variable fragments (scFvs) binding domain of CD3 molecules, could redirect cytotoxic T cells to kill tumor cells. The IgG-scFv format of BsAb is a dual bivalent and asymmetrical design, which adds the benefit of potent cytotoxicity and less complicated for manufacture but limits the stability and production. Here, we engineered a series of interchain disulfide bonds in the Fab region of IgG-svFv BsAbs and evaluated its biophysical and biological properties. We found that simultaneously replaced the position of VH 44 -VL 100 and CH1 126 -CL 121 residues with cysteine, to form two additional disulfide bonds, could markedly increase monomeric BsAb formation and yield. The thermostability and stability against aggregation and degradation also performed better than BsAbs without extra disulfide bonds introduction. Besides, the affinity of engineered BsAbs was maintained, and the h8B-BsAb antibody had a slight enhancement in an inhibitory effect on target cells.